Eroticism Organization in Independent Contemporary Dance in Paravachasca Valley (Córdoba, Argentina) - Francisco Miguel Fernando; Bertea, Francisco Miguel Fernando; Francisco Miguel Fernando (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2023)
In the field of Social Studies of the Arts, numerous studies investigate the sexuality and eroticism of different dances in Argentina (for example, tango, electronic music, cuarteto, etc.). However, we identify a vacancy area regarding Contemporary Dance. In this article, we investigate the native meanings of eroticisms in the field of independent contemporary dance in the Paravachasca Valley (Córdoba, Argentina) through a collaborative ethnographic methodology. We carried out observant participation work between 2018 and 2022, from a corporeal approach, and we interviewed eight dancers who perform different gender identities (cis, bisexual and trans). We employed a reflective and collaborative data construction process of co-interpretation and co-theorization, with the contribution of grounded theory. We identify an expanded notion of eroticism, characterized by plurality, pleasure and not reduced to sexuality. Analytically, we distinguish three types of eroticism (sexual, sensual and aesthetic), which are realized in a unique and dynamic way in each dancer. Eroticisms are organized under a regime of concealment and discretion, based on the ethos and micropolitics of this field of art, which makes up an affective culture. One of its composition lines is an ethics of care, related to a feminist ethics. Thus, this analysis seeks to contribute to the study of eroticism in contemporary dance, and does so from the interior of the province.